A Multi-Criteria decision making (MCDM) methodology for high temperature thermochemical storage material selection using graph theory and matrix approach - Sahand Hosouli (Materials and Design, 2023)
Industrial waste heat is currently underutilized due to the techno-economic challenges, inherent variability and intermittency of this source. To overcome the existing barriers, reduce the emission of greenhouse gases and protect the global environmental conditions, energy recovery is one of the most effective strategies. In the design of heat storage systems, the material selection procedure plays an important role and requires complex interrelationships between the various factors and parameters to be elucidated toachieve the best candidate material for a given application. This paper presents a Multi-Criteria Decision Making (MCDM) methodology based on Graph Theory and Matrix approach for high temperature thermochemical storage (TCS) material selection. Furthermore, the presented approach has been used to select the suitable candidate material for recovering the high temperature waste heat (over 500 °C) in Port Talbot Steelworks.